Bottled tomato sauce from six varieties of tomatoes (Lycopersicon esculentum) - Villa-real, Bernadette B.; De Leon, Sonia Y. (1985.)
Six local varieties wee evaluated for use in processing tomato sauce. Of these six, Pito and Sprinter varieties were determined to be the two best varieties having an average moisture content 92.7% and 92.6%; pH of 4.09 and 4.03; and a total solid content of 7.1 and 6.1% respectively. The tomato sauce samples from the Pito and Sprinter varieties and a commercially available tomato sauce were compared and the Kramer's Rank Sum Test was conducted. Results showed that at the 5% level of significance the tomato sauce sample from the Pito variety was significantly more preferred than those pf Sprinter variety and commercial brand of tomato sauce. The tomato sauce sample from the Pito variety had a Munsell Color Value of 5R 4./10, a total solids content of 32.5%, a moisture content of 46.18%, a consistency of 1.86 poise at a shear rate of 20, a pH of 3.5, a a 0% mold count. It was sensorially evaluated to have a bright red color, a slight tomato flavor, a burnt tomato odor, a thick consistency, an a general acceptability of like moderately to like slightly.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tomatoes; Tomato sauce